GREEN BUILDING TOWARD CONSTRUCTION SUSTAINABILITY: ENERGY EFFICIENCY WITH MATERIAL AND DESIGN ASPECTS (Journal of Technology and Operations Management, 2017)
In this globalization era, sustainable constructions have taken on some new steps to stimulate green building practice. Green building criteria basis are energy efficiency, material and resource conservation and sustainable design of the building itself. Energy efficiency still has a long way to go, due to some barriers that prevail in the practice of energy efficiency. Similarly, materials and design that are originally used have created various issues related to the environment and human health. In Malaysia, people’s level of awareness about green building is still low and they have minimum understanding and lack of familiarity about green materials and sustainable design. According to Klufallah, Nuruddin, Khamidi and Jamaludin (2014), 24% of total of carbon dioxide (CO2) comes from the construction sector in the Malaysia. Therefore, this study aims to look into building energy efficiency and materials and design employed in green buildings to achieve constructive sustainability and to establish the benefits of utilising energy efficiency, green materials and sustainable design. This study will be done using a case of the construction sector in Malaysia. The data will be collected through an interview with several Property Development Companies or projects that apply the green building criteria. The recommendation is that more property development companies should be interviewed so that more comprehensive results can be gathered.